A 430 kyr multi-proxy record of Eurasian Ice Sheet history and organic carbon burial in the eastern Eurasian Basin, Arctic Ocean - Ruediger Stein; Thomas Frederichs; Kirsten Fahl; Walter Geibert; Jens Matthiessen; Frank Niessen; Christoph Vogt; Cynthia Sassenroth; Evgenia A Bazhenova (PANGAEA, 2025)
Sediment Core PS115/2-2 was recovered from the Amundsen Basin in 3600 m water depth at the eastern flank of the Gakkel Ridge during Polarstern Expedition PS115/2 in 2018 (Stein, 2019). The well-dated core is characterized by prominent organic carbon (OC) cycles and allowed for the first time to reconstruct in detail the interrelationship between ice-sheet dynamics and OC burial in the central Eurasian Basin during the last 430 kyr, and to correlate marine and terrestrial records of the Eurasian Ice Sheet (EIS) history. Our age model, a fundamental prerequisite for any kind of paleoclimatic reconstruction, is based on records of the inclination and relative paleointensity (RPI) of the Earth extquotesingles magnetic field approved by rock magnetic data, 230Th and 231Pa excess (230Thex and 231Paex) records, and AMS14C ages. Using geochemical and mineralogical proxy data, we could demonstrate that within pulses of EIS advance and retreat during glacial to subsequent deglacial times, erosion of sub-glacial ancient (petrogenic) OC-rich sedimentary rocks and soils delivered sediments that were transported onto the shelf and further across the shelf edge towards the Eurasian Basin. Subsequent mass-wasting processes were responsible for down-slope transport towards the deep sea, and long-distance transport of the fine-grained OC-rich suspension by contour and turbidity currents probably caused elevated burial of terrestrial OC in the deep Eurasian Basin. These significantly increased glacial OC-burial rates coincide with anoxic sedimentary conditions that allowed preservation of more labile algae-type OC. Its presence demonstrates that even during strong glacial episodes there must have been at least occasionally open-water (polynya-type) conditions along the Eurasian continental margin with marine and sea-ice algae productivity in front of the ice sheet, demonstrating that km-thick ice shelves were not a permanent feature of the central Arctic Ocean during major glaciations.